Preface - Terra, Ana Lúcia; Carvalho, Milena; Todorova, Tania; Rodríguez López, María Carmen (Bobcatsss, 2023)
This Conference Proceedings provides an overview of all selected papers, that were presented at BOBCATSSS 2021 Virtual Conference, 21st-22nd January 2021, on the main theme "Digital Transformation" (https://bobcatsss2021.sciencesconf.org/). The conference was jointly organized by the Porto Accounting and Business School - Porto Polytechnic (ISCAP), Portugal, University of Library Studies and Information Technologies (ULSIT), Sofia, Bulgaria and University of Leon, Spain. BOBCATSSS is an international annual symposium which addresses hot topics for librarians and information professionals in a fast-changing environment. It is created by and for students, teachers, researchers and professionals in the information field. BOBCATSSS is held under the auspices of BOBCATSSS Association (https://bobcatsss.info/, former EUCLID (European Association for Library and Information Education and Research). It is a tradition which has been passed on from one European country to another since 1993, providing a rich professional conference, accompanied by numerous opportunities for networking, personal exchanges, discussions, and learning. The 29th conference of BOBCATSSS was a virtual edition, due to the COVID-19 worldwide crisis. “DIGITAL TRANSFORMATION” was chosen as the theme for BOBCATSSS 2021. Information and communication technologies have a great impact on society, namely concerning the immediacy of access to information, the constant increase in the available information volume, the automation of services, the dematerialization of processes, the change in supports and formats, the attention to the client and changes in the behaviour of individuals. These impacts are also felt in the way people interact with information, in professional, academic, personal and playful terms. [...]